Opening science and innovation: Opportunities for emerging economies - Ottonicar, Selma Leticia Capinzaiki [UNESP]; Arraiza, Paloma Marín [UNESP]; Armellini, Fabiano (National Research University, Higher School of Economics (HSE), 2020)
Open innovation allows partnerships between business through knowledge sharing. The mission of open science is to encourage information sharing about academic research. The purpose of this paper is to demonstrate the relevance of open science to open innovation and vice versa, especially in the context of emerging economies. Furthermore, it aims to show the results of the intersection between university and innovation companies. The methodology was based on a systematic literature review to understand how researchers have been studying the subject. It also focuses upon the relevance of open innovation and open science to the business management and information science fields. Therefore, the connection between open science and open innovation is fundamental to encouraging partnerships between businesses and universities. This kind of partnership contributes to the economy of developing countries, so business can become more competitive.
Keywords: Business management; Business partnership; Developing countries; Emerging economies; Information science; Innovation; Open innovation; Open science; Systematic literature review; University and company